An analytical method to generate walking pattern of humanoid robot - Oh, Y.; Ahn, K.-H.; Kim, D.; Kim, C. (IECON Proceedings (Industrial Electronics Conference), 2006)
An analytic method to generate the real-time trajectory of the center of mass (CoM) is proposed for given zero moment point (ZMP) pattern. The whole walking process is divided into transient and periodic walking phases. For each phase of walking, we compute the analytic solution of the center of mass for given ZMP based on the inverted pendulum model. Specially, for the transient walking phase, we actively utilize the non-minimum phase solution to extract the center of mass trajectory. The proposed pattern generation method were implemented to a real humanoid robot system called by MAHRU-II. Those are verified by the experiments. ？ 2006 IEEE.